2017
DOI: 10.1038/s41598-017-04681-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual activation of neuronal G protein-gated inwardly rectifying potassium (GIRK) channels by cholesterol and alcohol

Abstract: Activation of G protein-gated inwardly rectifying potassium (GIRK) channels leads to a hyperpolarization of the neuron’s membrane potential, providing an important component of inhibition in the brain. In addition to the canonical G protein-activation pathway, GIRK channels are activated by small molecules but less is known about the underlying gating mechanisms. One drawback to previous studies has been the inability to control intrinsic and extrinsic factors. Here we used a reconstitution strategy with highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 70 publications
5
56
0
Order By: Relevance
“…The observed monoexponential decay curve was fit to a rate of K + conductance of 0.0098 ± 0.0002 s −1 . This rate is comparable to that observed for other K + channels using this assay (44). To further confirm the channel in POPC:POPG is not just exhibiting basal activity, we performed a series of assays as a function of the concentration of phosphatidylinositol 4,5-bisphosphate (PIP 2 ), a known inhibitor of KirBac1.1 (32,57).…”
Section: Resultssupporting
confidence: 75%
“…The observed monoexponential decay curve was fit to a rate of K + conductance of 0.0098 ± 0.0002 s −1 . This rate is comparable to that observed for other K + channels using this assay (44). To further confirm the channel in POPC:POPG is not just exhibiting basal activity, we performed a series of assays as a function of the concentration of phosphatidylinositol 4,5-bisphosphate (PIP 2 ), a known inhibitor of KirBac1.1 (32,57).…”
Section: Resultssupporting
confidence: 75%
“…Although the residual current displayed slower deactivation kinetics that might presume involvement of ERG channels (Wang et al, 1998;Gustina and Trudeau, 2009;Larsen, 2010), addition of the ERG channel blocker E-4031 (10 M) to the bath and internal pipette solutions did not significantly alter that current amplitude (t (28) ϭ 0.6, p ϭ 0.55) nor the deactivation currents (t (28) ϭ 0.98, p ϭ 0.65, n ϭ 15 cells) in DGGCs ( Fig. 1 E, F ), perhaps suggesting another member of the EAG channel family that is insensitive to E-4031, such as Elk2 (KCNH3/K v 12.2) (Saganich et al, 2001;Gessner and Heinemann, 2003).…”
Section: Channels and Erg Channels Have Differential Fractional Conmentioning
confidence: 96%
“…Although the ethanol-bound population of GIRK is expected to be about 1.8%, assuming a blood ethanol concentration of 18 mM, which is relevant to human consumption (10), it has been proposed that a relatively small increase in the K + current could have a substantial effect on the membrane excitability of neurons, by lowering the equilibrium potential and drawing farther from the firing threshold (9). Furthermore, functional analyses of GIRK by Slesinger's group have suggested that the ethanolinduced activation of GIRK can be cooperatively potentiated by other activators of GIRK, such as PIP 2 and cholesterol, which are usually present in native cell membranes (15,22). Thus, the activated fraction of GIRK under physiological conditions is expected to be higher than that calculated using the in vitro K d value obtained from our NMR analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the βγ subunit of G protein (Gβγ) released upon the activation of G-protein-coupled receptors, ethanol is known to directly open GIRK. The opening of GIRK is invoked by ethanol at physiologically relevant concentrations (on the order of 10 −2 M, or 0.1% blood alcohol level), and behavioral studies have shown that weaver mutant mice, which have mutated GIRK with impaired K + selectivity, and GIRK knockout mice exhibited diminished ethanol-induced analgesia (8,10,(13)(14)(15). These observations indicate that the opening of GIRK by ethanol is closely related to the ethanol action in vivo.…”
mentioning
confidence: 94%